ChemInform Abstract: Homologative Trifluoromethylation of Acetals. Issue 42 (1st October 2013) - Hamilton, James Y.; Morandi, Bill; Carreira, Erick M.
Abstract A method to synthesize different substituted α‐trifluoromethyl acetals via an insertion strategy is developed.